(untitled) (Journal of the College of Basic Education, 2022)
The pioneers poets are not creative in the employment of women creative element, poets are stepping in the imagination in the world of creativity, looking for elements of artistic themes through which to draw their vision and tormented suffering, trying to find them a creative world through which they enjoy themselves, and women and through Literary Ages One of those elements adopted by the poets is a narcissistic start that stems from the poet’s conscience to embody his aspirations on a paper he sees as hope, pain, sacrifice, fatherhood, and a bright future that includes the poet’s world. He seeks to achieve it. The modest research has tried to stand up to women’s creative element in the poets pioneer was entitled (elements of creativity in the poetry of pioneers model women), and the first was entitled (Women and the field of love in poetry) And the third was [the analogy and its effect in embodying the image of the beloved woman in the poetry of the pioneers]. The second section was entitled " Women and the field of sacrifice and struggle in the poetry of pioneers), and in The second topic is entitled "Women in the field of sacrifice and struggle in the poetry of pioneers", and the second is "the mechanisms of language in the image of women struggling in the poetry of pioneers." Then came the third topic entitled "Women and Social Suffering in the Poetry of Pioneers" Which stumbled by the footsteps of women, women excluded, loss and displacement, pyramid and old age], and then concluded the research conclusion, and a list of sources and references